Editorial: climate change and society - Alves, Fátima (2022)
Climate change presents one of the greatest challenges of the 21st Century. It will massively affect human societies in complex and multiple ways. And it seems to be almost uncontrollable in the near future. Our knowledge of the chemistry and physics of climate change, its causes and its consequences for planetary systems, is far greater than our understanding of the societal changes it poses. Climate change results from a complex process of societal transformations, which we all need to understand to better cope with the challenges it presents. Climatic conditions play a significant role and interfere with people’s lives in multiple ways. The causes are essentially known, based on unequivocal human action. All solutions also involve human decision and action. It is social and human action in both individual and social settings that are decisive for the future pathways of climate change and its disentanglement. There is also a factor of climate injustice that must be addressed. The nations that contributed most to the problem are often those that experience more limited and manageable consequences while those who contributed the least are often the most affected, vulnerable and unprepared. With climate change, the risk of conflicts, disasters and internal displacement increases so exacerbate existing inequalities and poverty. This presents a moral conundrum of the highest order. At the ecological level, the destruction or disintegration of nature/nurture is more visible, with strong impacts on the availability and reduction of natural resources. In terms of social systems, climate change breaks down social organization, housing, the food system, generates migration, increases economic losses, hunger and public health breakdowns. In a more invisible way, climate change destroys cultural belonging and individual and collective identities. In addition to these expected impacts in the most diverse social, cultural, economic and environmental sectors, human health has emerged as an important area of considerable alarm. Although not frequently mentioned or targeted as a key political concern, it is expected that the impact of climate change on human health will be severe, both in the proliferation and incidence of diseases. Moreover, climate change will have extensive implications to human wellbeing, which will reflect on social structures and ways of life.